Peran Guru Dalam Mendorong Inovasi Siswa Melalui Metode Pembelajaran Berbasis Proyek - Chandra Sagul Haratua; Uban Subandi; Leni Nurlela; Aji Sari Nusetyawati; Nurhikmah Fitriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to explore the role of teachers in encouraging student innovation through project-based learning methods in junior high school. This study uses a descriptive research approach to understand the experiences and views of teachers and students. The data used is qualitative data. The subjects of this research are Madrasah teachers, namely junior high schools, namely MTsS SA Al-Mukarrim. Data collection techniques and instruments through interviews, observations, and document studies. Based on the research, the findings show that teachers have an important role as facilitators, mentors and supervisors in the learning process. Teachers encourage students to experiment, identify problems, and design problem solving. The application of learning approaches is very effective for teachers in developing students' creativity, critical thinking, and innovation through project-based learning methods.